Emotional Dimensions of Music and Painting and their Interaction. (20th July 2015) - Campos-Bueno, J. J.; DeJuan-Ayala, O.; Montoya, Pedro; Birbaumer, N.
Abstract: Usually it is accepted that human manifestations such as music or painting share a common artistic trait. However, very little is known about the genetic, behavioral, developmental and neurobiological basis of such a musical-pictorial "universal". In an attempt to approach commonalities and differences between the psychology of music and pictorial art in Experiment 1 we investigated the emotional dimensions valence and arousal in a large sample ( N =156, M age = 21, 44 years, SD = 3, 89 years, range = 16–35 years) using a representative selection of musical and pictorial artistic stimuli. We found a stronger variability of valence and arousal with paintings and stronger effects of music on valence. In Experiment 2 ( N =202, M age = 21, 35 years, SD = 3, 57 years, range = 16–35 years) we present first quantitative data on the interaction between the two artistic categories of stimuli on a behavioral level, again observing effects of pictorial art and music on valence and arousal. Furthermore in Experiment 2 we replicated a more pronounced effect of music on the valence of pictures, particularly on positive valence the results of the ANOVA showed an increase in group A2: F (1, 120) = 6.23, p < .05, in group C2: F (1, 120) = 89.03, p < .001, and a surprisingly emotionally negative influence of pleasant paintings on the positive valence of music, group A1: F (1, 127) = 19.69, p < .001. Despite the unresolved problem of non-representativeness of the stimuli and the sample selected these results may suggest superior emotional "power" of music over painting.